2008 9th International Conference on Solid-State and Integrated-Circuit Technology 2008
DOI: 10.1109/icsict.2008.4734819
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic III-V/Si integration

Abstract: We summarize our work on creating substrate platforms, processes, and devices for the monolithic integration of silicon CMOS circuits with 111-V optical and electronic devices. Visible LEDs and InP HBTs have been integrated on silicon materials platforms that lend themselves to process integration within silicon fabrication facilities. We also summarize research on tensile Ge, which could be a high mobility material for III-V MOS, and research on an in-situ MOCVD Ah03/GaAs process for III-V MOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Based on the epitaxial lift-off and transfer technology, the researchers realized the monolithic integration of the digital control switch circuit of GaAs PHEMT and Si CMOS as illustrated in Figure 8(b) [58]. It has been reported that InP heterojunction bipolar transistors (HBTs) can be integrated on Si materials platforms within silicon fabrication facilities [59], as presented in Figure 8(c). Based on the ion-cutting technology [60][61][62][63], the researchers realized different kinds of wafer scale heterogeneous integration materials, e.g., GaAs/Si, InP/Si, LiTaO 3 /Si, LiNbO 3 /Si, SiC/Si, and Ga 2 O 3 /SiC, as shown in Figure 8(d).…”
Section: Cross-dimensional Heterogeneous Integrationmentioning
confidence: 99%
“…Based on the epitaxial lift-off and transfer technology, the researchers realized the monolithic integration of the digital control switch circuit of GaAs PHEMT and Si CMOS as illustrated in Figure 8(b) [58]. It has been reported that InP heterojunction bipolar transistors (HBTs) can be integrated on Si materials platforms within silicon fabrication facilities [59], as presented in Figure 8(c). Based on the ion-cutting technology [60][61][62][63], the researchers realized different kinds of wafer scale heterogeneous integration materials, e.g., GaAs/Si, InP/Si, LiTaO 3 /Si, LiNbO 3 /Si, SiC/Si, and Ga 2 O 3 /SiC, as shown in Figure 8(d).…”
Section: Cross-dimensional Heterogeneous Integrationmentioning
confidence: 99%
“…On the other hand, III-V materials and their compounds have led to the development of recent optoelectronics and optical communications owing to their outstanding light-emitting properties [4][5][6]. Therefore, one of the approaches that receives increased attention lately is that to integrate III-V materials or their compounds monolithically on Si [7][8][9][10][11]. This approach is anticipated to have the advantages of both the technologies and hence achieving improved device performance along with energy efficiency, package density and product cost [12,13].…”
Section: Introductionmentioning
confidence: 99%